Obstructive fibrinous tracheal pseudomembrane in a cat. (24th October 2020) - Nivy, Ran; Brenner, Ori; Shub, Vered; Bruchim, Yaron
Abstract: Tracheal intubation (TI) is a common procedure that rarely entails life‐threatening complications. A 1.5‐year‐old female spayed cat presented with acute signs of respiratory distress 5 weeks after undergoing TI. Radiographs revealed a marked, segmental, tracheal narrowing. A hard, 5‐cm‐long, white‐yellowish tissue was identified and removed from the trachea, with subsequent resolution of clinical signs and radiographic changes. Microscopically, the tissue consisted of fibrin and lytic neutrophils, interspaced with optically empty cavities and a few remains of talcum powder and hair shafts. Consequently, a diagnosis of obstructive fibrinous tracheal pseudomembrane (OFTP) was made. A rare complication of TI in humans, OFTP should also be suspected in cats with respiratory distress, a history of TI and radiographic evidence of tracheal narrowing. Based on cases from other species and the cat described herein, the condition can be easily resolved with OFTP removal.